Tidal zone effects on the diet composition of leaf-eating crabs in natural mangrove communities: a stable isotope analysis - Lu, Xiaoyan; Gu, Xuan; Zhang, Lin; Zhang, Jinhan; Wang, Wenqing; Wang, Mao (Frontiers in Marine Science, 2024)
Background In natural mangrove communities, mangrove species are often distributed zonally. Leaf-eating crabs are one of the most abundant and iconic arboreal brachyurans in mangrove forests, but variation in the composition of crab diets in different mangrove tidal zones is unknown. Methods To determine the contributions of mangrove leaves and other organic carbon (C) sources to leaf-eating crab diets, dual stable C and nitrogen (N) isotope signatures (δ13C and 1δ5N) were used in a Bayesian stable isotope mixing model. We conducted experiments at various tidal levels in the Dongzhaigang Bay National Natural Reserve in China. We analyzed δ13C and δ15N of leaf-eating crabs, mangrove leaves, sediment organic matter (SOM), and animal tissues (prey). Results The food composition of the dominant crab species, Parasesarma continentale, exhibited significant differences among the four tidal zones. From the margin to the high tide zone, the main food source shifted from predominantly mangrove leaves and SOM to primarily SOM and animal tissues. We observed a significant negative relationship between the C/N ratios of mangrove leaves and the proportion of leaves consumed by leaf-eating crabs. Additionally, as the tidal level increased, the C/N ratio of mangrove leaves also increased, whereas the proportion of leaves consumed by crabs decreased. Conclusion Leaf-eating crab diets vary significantly across tidal zones, highlighting the importance of considering tidal zone differentiation when studying consumer diets in mangrove ecosystems.